Recruitment Strategies and Challenges in a Pilot HIV Prevention Study among Cisgender Black Women in Houston, Texas - Couture, Lucy; Agyei, Abena; McCants, Shadawn; J. Hill, Mandy (Journal of Clinical Research In HIV AIDS And Prevention, 2025)
Recruitment for research studies focused on communicable diseases such as HIV (Human Immunodeficiency Virus) has historically been challenging, particularly among populations who have been underrepresented in media messaging, yet maintain a significant vulnerability to new HIV cases, like Black women. This study examines the recruitment strategies utilized in Aim 2 of pilot study at the University of Texas Health Science Center (UTHealth) in Houston, Texas that was funded by the Ujima Mentoring Program to develop, implement, and evaluate a video log (vlog)-based intervention. The overarching goal of the pilot study was to promote the uptake of pre-exposure prophylaxis (PrEP) among cisgender Black women in Harris County, Texas. Aim 2 involved the creation of a culturally relevant vlog for use in Aim 3, which sought to educate and motivate participants to consider PrEP as an HIV prevention strategy. With the growing role of digital platforms in public health outreach, social media was employed alongside traditional recruitment methods such as flyers and word-of-mouth referrals. Despite an expanded online reach, engagement remained low, and participation rates did not increase proportionally to the number of individuals who viewed recruitment materials. The reluctance to participate was largely attributed to stigma surrounding HIV and concerns about being publicly associated with an HIV prevention study based on participants feedback to the research team. Even the availability of research incentives to encourage participation did not significantly improve recruitment accrual goals, particularly among healthcare providers who experienced limitations with eligibility due to institutional policies. This study underscores the need to better understand the social and cultural barriers that prevent Black women and healthcare providers from engaging in HIV prevention research. While digital recruitment strategies can enhance visibility to a larger audience, they must be supported with trust-building efforts, community partnerships, and culturally competent messaging to encourage meaningful participation. These findings point to the critical need for multi-faceted recruitment strategies that go beyond social media campaigns and actively build trust within communities, ensuring that HIV prevention research and interventions are both accessible and culturally resonant.
Keywords: Recruitment; Community Health; HIV prevention; pre-exposure prophylaxis (PrEP)